Avidity‐Based Selection of Tissue‐Specific CAR‐T Cells from a Combinatorial Cellular Library of CARs. Issue 6 (29th January 2021) - Ma, Peixiang; Ren, Ping; Zhang, Chuyue; Tang, Jiaxing; Yu, Zheng; Zhu, Xuekai; Fan, Kun; Li, Guanglei; Zhu, Wei; Sang, Wei; Min, Chenyu; Chen, Wenzhang; et al.
Abstract: Using T‐cell chimeric antigen receptors (CAR‐T) to activate and redirect T cells to tumors expressing the cognate antigen represents a powerful approach in cancer therapy. However, normal tissues with low expression of tumor‐associated antigens (TAAs) can be mistargeted, resulting in severe side effects. An approach using a collection of T cells expressing a diverse, 10 6 ‐member combinatorial cellular library of CARs, in which members can be specifically enriched based on avidity for cell membrane antigens, is reported. Using CD38 as the target antigen, an efficient and effective selection of CARs specifically recognizing CD38 + tumor cells is demonstrated. These selected CAR‐T's produce cytokines known to be associated with T cell activation in a CD38 expression‐dependent manner. This avidity‐based selection endows the engineered T cells with minimal off‐tumor effects, while retaining robust antitumor efficacy both in vitro and in vivo. The described method may facilitate the application of CAR‐T therapy to TAAs previously considered undruggable. Abstract : A novel polyclonal combinatorial cellular library of chimeric antigen receptors provides a comprehensive coverage of immune responses to specific antigens in vitro. An efficient and effective avidity‐based selection strategy takes advantage of paracrine signaling systems in cell–cell interactions, which endow the engineered T cells with robust antitumor efficacy both in vitro and in vivo with minimal on‐target off‐tumor effects.